EXTREME LASER RADIATION: PHYSICS AND FUNDAMENTAL APPLICATIONS : Effect of a prepulse on the efficiency of gamma-ray generation by a relativistic laser pulse obliquely incident on a planar target. (31st March 2017) - Serebryakov, D A; Nerush, E N
Abstract: This paper examines the effect of a density gradient produced in a target by a prepulse on the efficiency of synchrotron gamma-ray generation by a laser pulse with an intensity of the order of 10 22 to 10 23 W cm -2 obliquely incident on a planar target. We demonstrate that the gamma-ray and hard X-ray generation efficiency and the fraction of absorbed laser pulse energy can exceed those in the case of a uniform target with a sharp boundary by a factor of 1.3 – 2, depending on the angle of incidence. At a moderately large preplasma size, the optimal angle of incidence is 30°. At a sufficiently large size, normal incidence is optimal.